Efeitos terapêuticos de um programa de atividade física em indivíduos com esquizofrenia : do comportamental ao biológico. - Barros, Meire Kelly Scalia [UNIFESP] (2019)
Introduction: Schizophrenia is i dentified as one of the most prevalent psychiatric disorders in mental health services. Medicine and movement sciences have sought to improve physical activity (PA) experimentation as an effective procedure for the prevention, treatment, and rehabilitation of mental disorders. The aim of this study was to verify the therapeutic effects of a Physical Activity Program ( on the levels of depression, anxiety, mood (questionnaires)and inflammation ( salivary IL 6 and TNF alpha) of individuals with schizophre nia. Methodology : A Physical Activity Program was performed for 12 weeks, twice a week, with an average duration of 45 minutes each session and aerobic emphasis. Participants were 32 individuals diagnosed with schizophrenia; 15 females and 17 males, divide d into Control Group ( CG , n = 11, did not participate in the FAP )); Intermediate Group I G , n = 10, performed less than 70% of sessions and Exercise Group EG , n = 11, performed more than 70% of sessions). The volunteers signed an informed consent form and filled out anamnesis form with personal, health and PA level data. The following questionnaires were applied before and after the PAF: Beck Depression Index, State Trait Anxiety Inventory ( and Bru nels Mood Scale (BRUMS), and saliva collection (froze n at 80ºC until analysis with Kit Elisa).Statistical analysis: After normality tests, Kruskal Wallis test was performed for analysis between groups and Wilcoxon test for intragroup analyzes. Results : About 59% of the sample (n = 19) was classified as se dentary; 32% (n = 11) as irregularly active and only 6% (n = 2) of the sample was physically active. After the Physical Activity Program , there were no significant anthropometric changes in any of the groups. There was a statistically significant reduction (p <0.05) within the group for the variables BDI p = 0,008), STAI Trait ( p =0,040 ), subvariable “depression” of the BRUMS p = variable and IL 6 p = level only in the EG. The CG showed a significant reduction in the sub variable “vigor” of the BR UMS variable p = Discussion : The regular practice of PA proved to be an interesting component for the treatment of individuals in psychological distress, considering the results presented in the research and the physical, metabolic and mental harms that sedentary habits can cause. Corroborating literature data, the sedentary or inactive profile of most individuals in this study contributes to the maintenance of negative psychobiological symptoms. Conclusion : The implementation of a simple PA practice program was able to promote favorable therapeutic effects in the participants, regardless of anthropometric changes. Further studies are needed with the control of other variables and forms of exercise to analyze and better understand all the benefits tha t PA practice can provide for schizophrenic practitioners.